VD_FINDINFO Faillite / 2012 / 44 vom 29. März 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, PROLONGATION DU DÉLAI, OBSERVATION DU DÉLAI, AVANCE DE FRAIS | 101 al. 3 CPC (CH), 98 CPC (CH)